Final Wishes: End-of-Life Decisions - Martie Gillen; Carolyn S. Wilken (EDIS)
As you grow older, you should discuss your final wishes with your family members so they will know what type of medical care you will want. The Five Wishes program and brochure present an easy way to communicate these decisions to your family and create a legal document. This revised 3-page fact sheet was written by Martie Gillen and Carolyn S. Wilken, and published by the UF Department of Family, Youth and Community Sciences, August 2012.